2009
DOI: 10.1590/s1413-35552009005000035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pursed-lip breathing on heart rate variability and cardiorespiratory parameters in subjects with chronic obstructive pulmonary disease (COPD)

Abstract: Influence of pursed-lip breathing on heart rate variability and cardiorespiratory parameters in subjects with chronic obstructive pulmonary disease (COPD) Influência da respiração freno-labial sobre a variabilidade da frequência cardíaca e parâmetros cardiorrespiratórios em pacientes com doença pulmonar obstrutiva crônica (DPOC) Ramos AbstractObjectives: To assess the effects of pursed-lip breathing (PLB) at rest on the behavior of heart rate (HR) and its variability, and on variations in blood pressure (BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 34 publications
(40 reference statements)
2
38
0
5
Order By: Relevance
“…Tug et al 45 found no significant difference between mild and moderate-to-severe COPD groups for the isolated parasympathetic, sympathetic, or mixed form (P Ͼ .05). Similarly, Ramos et al 29 Two studies of high methodological quality assessed the influence of disease duration on autonomic function in subjects with COPD, and both studies concluded that it had none (P Ͼ .05). 17,45 Furthermore, one study of high methodological quality indicated that COPD exacerbation was associated with a significant increase in LF, HF, LF/HF, and TP (P Ͻ .05) compared with subjects with stable COPD and/or healthy controls.…”
Section: Factors Influencing Autonomic Function In Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tug et al 45 found no significant difference between mild and moderate-to-severe COPD groups for the isolated parasympathetic, sympathetic, or mixed form (P Ͼ .05). Similarly, Ramos et al 29 Two studies of high methodological quality assessed the influence of disease duration on autonomic function in subjects with COPD, and both studies concluded that it had none (P Ͼ .05). 17,45 Furthermore, one study of high methodological quality indicated that COPD exacerbation was associated with a significant increase in LF, HF, LF/HF, and TP (P Ͻ .05) compared with subjects with stable COPD and/or healthy controls.…”
Section: Factors Influencing Autonomic Function In Subjectsmentioning
confidence: 99%
“…Four studies of low 26,29 and high 37,45 methodological quality evaluated the influence of disease severity on autonomic function in subjects with COPD. Two of the studies concluded that disease severity had a significant effect on autonomic function.…”
Section: Factors Influencing Autonomic Function In Subjectsmentioning
confidence: 99%
“…Creemos además que es importante trabajar la musculatura periférica ya que los pacientes con EPOC se vuelven más sedentarios por la disnea en ejercicio y esto provocaría pérdida de masa muscular 22 . Por otra parte, es crucial la kinesiterapia respiratoria principalmente la aceleración del flujo espiratorio (aFe lento y rápido) más tos dirigida, para favorecer la eliminación de secreciones 8,23 y la rLF ya que esta última técnica desplazaría el punto de igual presión a vías aéreas menos colapsables, favoreciendo la salida del aire, disminuyendo así el atrapamiento aéreo y la hiperinsuflación pulmonar, lo cual reduce la disnea 24 , además esta técnica aumenta el volumen corriente y disminuye la frecuencia respiratoria 25 , se educa bastante en los pacientes para que la ocupen en momentos de exacerbación.…”
Section: Comentariosunclassified
“…Os Quadros 1 e 2 descrevem os dez ensaios clínicos selecionados [11][12][13][14][15][16][17][18][19][20] . As duas revisões bibliográficas encontradas na busca realizada estão apresentadas a seguir de forma descritiva, por não possuírem a formatação estabelecida para a análise dos dados.…”
Section: Características Dos Estudos Selecionadosunclassified
“…Ramos et al 18 estudaram a manobra realizada durante o repouso e observaram que sua realização eleva o valor do índice de raiz quadrada da média do quadrado das diferenças entre intervalos RR normais adjacentes (RMSSD), indicativo da atividade parassimpática, quando comparado à respiração espontânea. Os autores inferem que a RFL diminui o balanço simpatovagal, o que pode ser decorrente da diminuição da f. Em função das alterações observadas em parâmetros cardiorrespiratórios e autonômicos, os autores ressaltam a importância da monitorização destes pacientes durante a realização da manobra.…”
Section: Respiração Frenolabial E Mecânica Respiratóriaunclassified